UPAYA MENINGKATKAN PEMAHAMAN KONSEP MATERI DIFUSI DAN OSMOSIS DENGAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA SISWA KELAS XI IPA DI SMA NEGERI 1 SEJANGKUNG - MINDARIATI, SP (Yudha English Gallery, 2021)
This study aims to analyze whether or not the effect of the application of the Problem Based learning model with diffusion and osmosis material on the improvement of conceptual understanding and learning outcomes of class XI IPA students at SMA Negeri 1 Sejangkung. This research is a Classroom Action Research (PTK) using qualitative descriptions.The research subjects were students of class XI Science Senior High School 1 Sejangkung. Data collection was carried out by observation and test techniques. Data analysis in this research is using qualitative descriptive analysis. Based on the results of the study it was concluded that there was an increase in the implementation of learning, which was evidenced by an increase in understanding of the concept of student learning, the percentage of cycle I was seen in the increase in value, from 72.22% to 86.11% so that there was an increase of 13.89%. Student responses to problem-based learning models on diffusion and osmosis material in class XI Science Senior High School 1 Sejangkung, Sambas district, show very good criteria. And this can be seen also in student learning outcomes increased by 8.33% from 75% to 83.33% The conclusion is that the application of the Problem Based learning model is feasible to use as a teaching material on diffusion and osmosis material and gets a very good response category.